Reflections on water: architectural manifestations in the historic and cultural quarter along Lake Pichola in Udaipur - Samant, S. (Canadian Center of Science and Education, 2010)
The aim of this paper is to undertake a critical appreciation of the historic cultural quarter along the eastern edge of Lake Pichola in Udaipur, which is a result of its unique context with the objective of understanding the forces that underpin this development, examine its existing state, and highlight key concerns. The main issues that were highlighted include preservation of existing traditions, conservation and adaptive reuse of historic structures, sensitive and participatory planning and design, formalising of street activities, provision of infrastructure, and administrative structures to deliver the project, and organisation of awareness programs for the local community.